Multi‐Atomic Layers of Metallic Aluminum for Ultralong Life Lithium Storage with High Volumetric Capacity. (15th May 2017) - Gu, Jianan; Li, Bin; Du, Zhiguo; Zhang, Chao; Zhang, Di; Yang, Shubin
Abstract : Metallic aluminum (Al) have been explored as potential anode materials for lithium storage because of its high theoretical capacity (993 mAh g –1 ) and low voltage plateaus. Al possesses high electric conductivity, low cost and environmental friendliness. Unfortunately, Al suffers from huge volume change (>100%) during the lithiation/delithiation process, which inevitably results in the pulverization of electrode and rapid capacity decay during cycling processes. To circumvent above issues, a simple but efficient strategy is demonstrated to fabricate free‐standing multi‐atomic layers of metallic Al by harnessing the good ductility of Al under pressure. The resultant multi‐atomic Al layers are ultrathin, ≈3 nm, and have a large aspect ratio. Such unique features enable multi‐atomic Al nanosheets to construct uniform and compact films with graphene. Thus, the hybrid films with different ratios are achieved, in which the notorious volume change of metallic Al can be efficiently circumvented via the good flexibility of graphene, and the density of whole electrode can be significantly enhanced. As a consequence, the optimized multi‐atomic Al layers‐graphene (AlL‐G) film exhibits a very high volumetric capacity of 1089 mAh cm –3, high‐rate capability and ultralong cycle life up to 20 000 cycles for lithium storage. Abstract : Multi‐atomic layers of metallic aluminum (Al) are successfully fabricated using a rolling method under high pressure. These ultrathin Al nanosheets could construct uniform films with graphene. The volume change of metallic Al can be alleviated via the flexibility of graphene, leading to a novel lithium‐ion battery anode with high volumetric capacity, high‐rate capability, and ultralong cyclic life up to 20 000 cycles.